PERAN KOMPETENSI SOSIAL GURU PAK TERHADAP SUASANA PEMBELAJARAN DAN MINAT BELAJAR SISWA KELAS IX DI SMP NEGERI II KAUDITAN - Adelin Langi, Elsjani; Ranting, Hermin; Kambong, Hizkia Joel; Nendissa, Julio Eleazer (Jurnal Kala Nea, 2024)
Facing the 5.0 era, Christian religious education is one of the important pillars for instilling social and cultural values in society. In the 21st century, science and technology have increased, requiring Christian religious education teachers to teach effectively while motivating students to actively learn. Teachers' social competence, including interpersonal skills, the ability to build positive relationships, and empathy are the main things in realizing a conducive learning process. The purpose of this study is to explore the obligations of Christian religious education teachers' social competence in creating a pleasant learning atmosphere and increasing the learning interest of grade IX students of SMP Negeri II Kauditan. Data were obtained through interviews with the principal, vice principal, teachers, and students. The author obtained results in the form of effective communication between teachers and students, harmonious relationships, and a supportive learning environment that contributed significantly to increasing student participation and motivation to learn. The conclusion obtained is that the success of Christian religious education teachers in creating a productive and interesting teaching atmosphere is highly dependent on the teacher's social abilities. Thus, teacher social competence is a crucial factor in encouraging active student involvement so that they can achieve effective and good learning outcomes.